Design and synthesis of new trimethoxylphenyl-linked combretastatin analogues loaded on diamond nanoparticles as a panel for ameliorated solubility and antiproliferative activity - Islam Zaki; Amal M. Y. Moustafa; Botros Y. Beshay; Reham E. Masoud; Mohammed A. I. Elbastawesy; Mohammed A. S. Abourehab; Mohamed Y. Zakaria (Taylor & Francis Group, 2022)
A new series of vinyl amide-, imidazolone-, and triazinone-linked combretastatin A-4 analogues have been designed and synthesised. These compounds have been evaluated for their cytotoxic activity against MDA-MB-231 breast cancer cells. The triazinone-linked combretastatin analogues (6 and 12) exhibited the most potent cytotoxic activity, in sub-micromolar concentration compared with combretastatin A-4 as a reference standard. The results of β-tubulin polymerisation inhibition assay appear to correlate well with the ability to inhibit β-tubulin polymerisation. Additionally, these compounds were subjected to biological assays relating to cell cycle aspects and apoptosis induction. In addition, the most potent compound 6 was loaded on PEG-PCL modified diamond nanoparticles (PEG-PCL-NDs) and F4 was picked as the optimum formula. F4 exhibited enhanced solubility and release over the drug suspension. In the comparative cytotoxic activity, PEG-PCL modified F4 was capable of diminishing the IC50 by around 2.89 times for nude F4, while by 3.48 times relative to non-formulated compound 6.